The use of Clinostomum complanatum (Trematoda: Clinostomidae) in freshwater fish as a bio indicator of some heavy metals conatmination from Sarchnar, Sulaimanyah city, Iraq - Ali, Muqdad (University of Thi-Qar Journal of agricultural research, 2025)
The aim of this study is to investigate the role of Clinostomum complanatum in freshwater fish as a bio indicator for the presence and concentration of some heavy metals from Sarchnar in Sulaimanyah city, Iraq. The parasite Clinostomum complanatum (Rudolphi, 1814) is a digenean trematode in the family Clinostomidae. Total of 35 Clinostomum parasites were collected from the gills of 13 infected fish specimens two leuciscid species: Squalius cephalus and Squalius lepidus from Sarchnar in Sulaimanyah city. The prevalence value of infection fish Squalius cephalus and Squalius lepidus was %20 and %16.66, respectively and the mean intensity of the parasite showed 2.87 and 2.4, respectively. The morphology of this parasite was illustrated using compound microscope. Moreover, some heavy metals (Cd, Cu, Pb, Zn and Fe) were analyzed in water and (Cd, Cu, Pb and Zn) were analyzed in parasite and the results showed the concentrations of Cd, Cu, and Pb at four sites were below the (LOQ), Iron (Fe) levels were also below the (LOQ) in sites 1 and 3 but in site 2 and site 4 were above the (LOQ); however, zinc (Zn) concentrations exceeded the (LOQ) in all sites.  Additionally, the concentration of Cd and Zn were deposited in parasite tissues more than water in all study sites. Cd was recorded its highest concentration 3174.7 mg/Kg above the (LOQ). The Clinostomum complanatum parasite could be used as bio indicators of heavy metals pollution of water.